2012
DOI: 10.1155/2012/951215
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Influence of Climate Change on Agroecosystem Services: Potential Impacts on Honey Yields in a Small-Island Developing State

Abstract: Global change poses numerous challenges to developing nations and small-island developing states (SIDSs). Among these are the effects of climate change on honeybees' provisioning services including honey production. Here we ask two questions. First, what is the relationship between honey yield and climate in a tropical environment? Second, how does yield vary spatially under current climate and future scenarios of climate change? Focusing on the island of Puerto Rico, we developed an ensemble of bioclimatic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
3
16
0
3
Order By: Relevance
“…Based on these differences we might anticipate that: tropical regions will 1733 experience less temporal decoupling of pollination services than temperate regions, temperate 1734 plant species with shorter flower life might benefit more from a warming-induced increase in 1735 pollinator activity than temperate species with longer flower life, and there may be an 1736 increase in pollination success of animal-dependent plants in the tropics due to increased 1737 pollinator activity in response to higher temperatures. 1738 Domesticated honeybees are expected to remain effective in tropical zones under the 1739 temperatures predicted for the next century, but foraging behaviour will be altered under 1740 increased rainfall, resulting in reduced productivity of honey and crops (Delgado et al, 1741(Delgado et al, 2012. It is likely that domesticated western honeybee races in warmer climatic conditions 1742 will need more intensive disease management than they currently do.…”
mentioning
confidence: 99%
“…Based on these differences we might anticipate that: tropical regions will 1733 experience less temporal decoupling of pollination services than temperate regions, temperate 1734 plant species with shorter flower life might benefit more from a warming-induced increase in 1735 pollinator activity than temperate species with longer flower life, and there may be an 1736 increase in pollination success of animal-dependent plants in the tropics due to increased 1737 pollinator activity in response to higher temperatures. 1738 Domesticated honeybees are expected to remain effective in tropical zones under the 1739 temperatures predicted for the next century, but foraging behaviour will be altered under 1740 increased rainfall, resulting in reduced productivity of honey and crops (Delgado et al, 1741(Delgado et al, 2012. It is likely that domesticated western honeybee races in warmer climatic conditions 1742 will need more intensive disease management than they currently do.…”
mentioning
confidence: 99%
“…The single colonization hypothesis Rico (Delgado et al, 2012;Rivera-Marchand, Oskay and Giray, 2012). The single colonization hypothesis Rico (Delgado et al, 2012;Rivera-Marchand, Oskay and Giray, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Abundance/ intensity of Varroa destructor infestation in honeybee colony is more important factor to establish its management level in honeybee colonies (Delgado et al , 2012;Okosun, 2013). The intensity (Number of varroa destructor/100 bees) was compared in three hive types: Traditional, Transitional and Frame (Table 4.8).The result showed that, there is no significant variation (F = 0.076, P>0.05) in abundance/intensity of the mite among hive types.…”
Section: Abundance Of Varroa Destructor In Different Hive Typesmentioning
confidence: 99%